A Quranic Science: al- Vucuuh va'n-Nazair - (:unkn) unknown (KARABUK UNIV, 2015)
Qur'an is a verbal and semantic miracle due to the fact that it is Allah's word. If the mankind and the jinns were together to produce the like of this Qur'an, they could not produce the like thereof, even the shortest chapter of it and even if they helped one another. That is because Allah's Word is the most beautiful one. Therefore, the sciences related to Quran is also the most valuable asset. Among the sciences of Quran is the science of al-vucuh and al-nazair. The science of al-vucuh deals with the words with multiple meanings whereas al-nazair is about the groups of words with same meanings but differing in written form and pronunciation. This science is about the linguistic explanation of Quran that every person engaged in commentaries of Quran (tafsir) should have a great knowledge about beside other sicences. In this article we studied the definition of this science, its importance, history and literature as well as its relations with other sciences.
Keywords: al-vucuuh; al-nazair; commonmeaning in Quran; oppositewords in Quran